IL-4 alpha chain receptor (IL-4Rα) polymorphisms in allergic bronchopulmonary sspergillosis - Consolino Judy D (Clinical and Molecular Allergy, 2006)
Abstract Background Allergic bronchopulmonary aspergillosis occurs in 7–10% of cystic fibrosis (CF) and 1–2% of asthmatic patients. HLA-DR restriction and increased sensitivity to IL-4 stimulation have been proposed as risk factors in these populations. Objective We examined for the presence of IL-4 receptor alpha chain (IL-4Rα) single nucleotide polymorphisms (SNPs) in ABPA and whether these accounted for increased sensitivity to IL-4 stimulation. Methods One extracellular (ile75val) and four cytoplasmic IL-4Rα SNPs were analyzed in 40 CF and 22 asthmatic patients and in 56 non-ABPA CF and asthmatic patients. Sensitivity to IL-4 stimulation was measured by induction of CD23 expression on B cells. Results IL-4Rα SNPs were observed in 95% of ABPA patients. The predominant IL-4Rα SNP was the extracellular IL-4Rα SNP, ile75val, observed in 80% of ABPA patients. Conclusion The presence of IL-4Rα SNPs, principally ile75val, appears to be a genetic risk for the development of ABPA.